An acute lytic cell death induced by xanthohumol obstructed ROS detecting in HL-60 cells. (February 2020) - Wang, Chun-Ming; Huo, Xiang; Chen, Jun; Liu, Jia-Wei; Yang, Ting-Yu; Mi, Xiang-Quan; Meng, Yue; Zhou, Li; Lin, Chang-Jun; Liu, Jing
Abstract: Serum is an important component in cell culture medium. It also possesses potent antioxidant properties. Therefore, the conventional protocols for detecting reactive oxygen species (ROS) in cultured cells with fluorescent probes include washing and suspending cells with serum-free buffers, such as PBS. This transient serum deprivation is essential for the ROS detecting. Unfortunately, it may also cause unexpected results, which push us to choose more optimal experiment conditions. In the present study, we found an acute lytic cell death induced by xanthohumol (XN), which obstructed ROS detecting in human leukemia cell line HL-60 cells. XN induced ROS burst, caused cell swelling, membrane permeability increase, LDH release, and ultimately an acute lytic cell death and cell rupture. These effects could be alleviated by the antioxidant N-Acetyl-L-cysteine (NAC). Apoptosis, pyroptosis or necroptosis were not observed in this process. Results also indicated that 2% serum addition had already completely scavenged ROS induced by 10 μM XN. Taken together, it is strongly suggested to detecting ROS in a serum-free medium when studying where and how ROS generated in cells. The concentration at the ROS maximum point (10 μM XN in this study) can be selected as the optimal concentration. Graphical abstract: Unlabelled Image Highlights: XN induced ROS, caused cell swelling and damaged cell membrane integrity. An acute lytic cell death was induced by XN treatment ultimately. This ROS-induced acute lytic cell death was not apoptosis, pyroptosis or necroptosis. Help to explain the unusual decrease of ROS generation found in pro-oxidant studies.